Evolving trends among Pseudomonas aeruginosa: a 12-year retrospective study from the United Arab Emirates - Thomsen, Jens; Menezes, Godfred A.; Abdulrazzaq, Najiba M.; , The UAE AMR Surveillance Consortium; Moubareck, Carole Ayoub; Senok, Abiola; Everett, Dean B. (Frontiers in Public Health, 2023)
Introduction Pseudomonas is a group of ubiquitous non-fermenting Gram-negative bacteria (NFGNB). Of the several species associated with humans, Pseudomonas aeruginosa (PA) can acclimate to diverse environments. The global frequency of PA infections is rising and is complicated by this organism's high intrinsic and acquired resistance to several clinically relevant antibiotics. Data on the epidemiology, levels, and trends of antimicrobial resistance of PA in clinical settings in the MENA/GCC region is scarce. Methods A retrospective 12-year analysis of 56,618 non-duplicate diagnostic Pseudomonas spp. from the United Arab Emirates (UAE) was conducted. Data was generated at 317 surveillance sites by routine patient care during 2010–2021, collected by trained personnel and reported by participating surveillance sites to the UAE National antimicrobial resistance (AMR) Surveillance program. Data analysis was conducted with WHONET (https://whonet.org/). Results Among the total isolates (N = 56,618), the majority were PA (95.6%). Data on nationality revealed 44.1% were UAE nationals. Most isolates were from soft tissue (55.7%), followed by respiratory tract (26.7%). PA was more commonly found among inpatients than among outpatients, followed by ICUs. PA showed a horizontal trend for resistance to fluoroquinolones, 3rd- and 4th-generation cephalosporins, and decreasing trends of resistance for aminoglycosides and meropenem. The highest percentage of multidrug resistant (MDR) isolates was reported in 2011 at 35.6%. As an overall trend, the percentage of MDR, extensively drug-resistant (XDR), and possible pandrug-resistant (PDR) isolates generally declined over the study period. Carbapenem-resistant PA (CRPA) were associated with a higher mortality (RR: 2.7), increased admission to ICU (RR: 2.3), and increased length of stay (LOS) (12 excess inpatient days per case), as compared to carbapenem-susceptible PA (CSPA). Conclusion The resistance trends in Pseudomonas species in the UAE indicated a decline in AMR and in percentages of Pseudomonas isolates with MDR and XDR profiles. The sustained Pseudomonas spp. circulation particularly in the hospital settings highlights the importance of surveillance techniques, infection control strategies, and stewardship to limit the continued dissemination. This data also shows that CRPA are associated with higher mortality, increased ICU admission rates, and a longer hospitalization, thus higher costs due to increased number of in-hospital and ICU days.